THE EFFECT OF INDIVIDUAL MORALITY AND INTERNAL CONTROL ON THE PROPENSITY TO COMMIT FRAUD: EVIDENCE FROM LOCAL GOVERNMENTS - Novita Puspasari; Eko Suwardi (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
This paper aims to examine the influence of individual morality and internal controls on individuals’ propensity to commit accounting fraud at the local government level. This is a quasi- experimental research paper. Individual morality and internal controls are hypothesized to be having an interaction with each other in influencing the propensity to commit accounting fraud. Individuals who have low levels of moral principles are hypothesized to have the tendency to commit accounting fraud in the absence of any internal controls. To test this, a 2x2 factorial experiment was conducted involving 57 students from the Masters in Economics Development programme at Gadjah Mada University. The result shows that there is an interaction between individual morality and internal controls. The absence of internal controls does not cause an individual with high moral principles to commit accounting fraud. However, individuals with low morality levels tend to commit accounting fraud when internal controls are absent. Keywords: Accounting Fraud, Morality, Internal Controls, Local Government